Pengembangan Modul Fisika Online Berbasis Web pada Materi Usaha dan Energi - Sari, Fitri Ana; Suseno, Nyoto; Riswanto, Riswanto (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
Human resources at school is good enough in utilizing technology, information, and communication online including in the field of education. Conditions on the ground show that in some schools in the learning is based online, but only limited scope blog and quipper school. For that we need to develop web-based online physics module on business material and energy. This research is R & D (Research and Development) model of ADDIE (Analysis, Design, Development, Implementation and Evaluation). The results showed that the level of feasibility according to the expert and the response of student’s who are on the criteria worth with a percentage of 85% and 72.5% respectively. The web-based online physics module can be used as a self-learning resource. This product, should be developed for other high school physics materials